A curious case of raised gradient across mitral bioprosthetic valve - Monish S Raut; Vijay Mohan Hanjoora; Murtaza A Chishti; Akhil Govil; Rakesh Pandey; Aman Jyoti; Ravi Kumar Mahavar; Shweta Suri Kandpal; Dileep Kumar Singh Rathor (Annals of Cardiac Anaesthesia, 2018)
High Doppler valve gradient is generally suggestive of valve thrombosis. However, it should be corroborated with the finding of restricted leaflet movement to confirm the diagnosis. In the present case, abnormally high gradient was not associated with limited leaflet movements or any valve thrombus.